Narrative bioethics and film. Some historical remarks - Cattorini, Paolo Marino (Medicina Historica, 2019)
The history of medicine, in synergy with other medical humanities, documents the relationships between technological progress, philosophy of care, and artistic vanguards. An important theoretical aspect is the contribution which narrative, in particular via the medium of film, provides not only to the clinical relationship (intended as a therapeutic alliance), but also to the ethical debate. An important instance of these relationships is seen in the evolution of the thinking of three important North American authors: Booth, Schrader, and Wiseman. Study of their works suggests, on the one hand, new lines of research in the fields of history, philosophy, and theology and, on the other hand, a consideration of new forms of clinical bioethics, drawn from aesthetic contributions. In fact, both clinical bioethics (which deals with actions) and film criticism (which deals with texts) seek to rationally justify an evaluation of either a moral or an artistic kind.